Ecological distribution of the shrimp Pleoticus muelleri (Bate, 1888) and Artemesia longinaris Bate, 1888 (Decapoda, Penaeoidea) in the southeastern Brazilian littoral - Batista, Abner Carvalho [UNESP]; Simões, Sabrina Morilhas [UNESP]; Lopes, Mateus [UNESP]; Costa, Rogério Caetano da [UNESP] (Sociedade Brasileira de Carcinologia, 2011)
The relationship between species abundance and environmental factors such as the bottom water temperature and salinity, the texture and organic matter content of the sediment and the distribution of Pleoticus muelleri and Artemesia longinaris were investigated. Specimens and samples of abiotic factors were collected monthly from May 2008 to April 2010 at 4 locations in Santos Bay on the southern coast of the State of São Paulo. A shrimp boat equipped with an otter-trawl net with an 8 m mouth aperture and a mesh size of 20 mm tapering to 18 mm at the cod end was used for sampling. Shrimp abundances were compared with an analysis of variance (ANOVA). However, when the data did not follow a normal distribution, we used the Kruskal-Wallis test. The relationship between environmental factors and the abundance of individuals was assessed with a Pearson's correlation. The largest catches of individuals of both species occurred in the late spring of 2008. The greatest abundance occurred at the outer part of the bay (collection point 4). The greatest abundance of P. muelleri was associated with lower temperatures and sediments with higher clay and organic matter content, whereas for A. longinaris, there was no significant correlation with any of the abiotic factors recorded. However, the occurrence of both species was related to lower bottom temperatures associated with the intrusion of the South Atlantic Central Water in the region.
Keywords: Abundance; Dendrobranchiata; Environmental factors; SACW